Decentralization and public service delivery in Nigeria - Okojie, Christiana (International Food Policy Research Institute, 2010)
Nigeria's efforts to decentralize its government system are aimed at improving service delivery. However, access to important social and economic services remains limited, especially for rural populations. The deficiencies in service delivery have been exacerbated by a strong urban bias in development policies and growing fiscal imbalances among the three tiers of government: national, state, and local. In particular, Nigeria faces a challenge in efficiently and effectively delivering agricultural and rural services at the local level to help the agricultural sector grow and alleviate poverty. To overcome this challenge, research suggests that the subnational governments, especially local governments, must be empowered with adequate tax and revenue authority to carry out their jurisdictional responsibilities. This brief summarizes existing knowledge on the decentralization of public service delivery to Nigeria's rural sector.